Implementasi Green Hospital di RSUD R. Syamsudin, SH dengan Kriteria Kerangka Kinerja Ekselen Malcolm Baldrige - Alatas, Haniah; Ayuningtyas, Dumilah (UI Scholars Hub, 2019)
The existence of green hospital is very necessary to overcome climate change which can cause disruption to human health and the environment, because hospitals are one of the contributors to pollution. RSUD R. Syamsudin, SH became a member of the Global Green and Healthy Hospital and is committed to implementing ten agendas, namely leadership, chemicals, waste, energy, water, transportation, food, pharmacy, buildings, and purchasing. Aim of this study is to analyze the implementation of green hospital with the Malcolm Baldrige Criteria Framework for Excellence Performance. Malcolm Baldrige Criteria evaluates based on seven criteria which isleadership, strategy, customer, measurement, analysis, and management of knowledge, labor, operations and results. The design of this study is qualitative by gathering information through in-depth interviews, questionnaires, and document review. Based on the results of research, the implementation of the green hospital in R. Syamsudin Hospital, SH received a score of 620.1 out of 1000 (maximum score) so that it was positioned in emerging industry leaders. The Leadership Criteria get the highest points, while the lowest points are the Customer Criteria. It can be concluded, RSUD R. Syamsudin, SH is in the average position in implementing green hospital, meaning that it already has several advantages but there are still several factors that can be improved so that the implementation of green hospital can be more optimal. For this reason, it was recommended to RSUD R. Syamsudin, SH to carry out routine evaluations, promote green hospital more aggressively, optimize hospital management information system, and strengthen the budget so that the achievement of ten agendas more optimized.